Analysis of Transmission Dynamics of Cholera: An Optimal Control Strategy - Adewole, Matthew O.; Onifade, Akindele; Ismail, Ahmad Izani Md; Faniran, Taye; Abdullah, Farah A. (Journal of Applied Nonlinear Dynamics, 2026)
Cholera affects populations living with poor sanitary conditions and has caused enormous morbidity and mortality. A mathematical model is presented for the spread of cholera with focus on three human populations; susceptible human, infected human and recovered human. The infected human population was subdivided into two groups - symptomatic individuals and asymptomatic individuals. We obtain the reproductive number and a sensitivity analysis of model parameters is conducted. The sensitivity analysis reveals key parameters which can be used to propose intervention strategies. Our analysis indicates that a single intervention strategy is insufficient for the eradication of the disease. Optimal control strategy is incorporated to find effective solutions for time-dependent controls for eradicating cholera epidemics. We use numerical simulations to explore various optimal control solutions involving single and multiple controls. Our results show that, as in related previous studies, the costs of controls have a direct effect on the duration and strength of each control in an optimal strategy. It is also established that a combination of multiple intervention strategies attains better results than a single-pronged approach since the strength of each control strategy is limited by available resources and social factors.